2014
DOI: 10.3390/insects5020301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Invasive Winter Moth Defoliation on Tree Radial Growth in Eastern Massachusetts, USA

Abstract: Winter moth, Operophtera brumata L. (Lepidoptera: Geometridae), has been defoliating hardwood trees in eastern Massachusetts since the 1990s. Native to Europe, winter moth has also been detected in Rhode Island, Connecticut, eastern Long Island (NY), New Hampshire, and Maine. Individual tree impacts of winter moth defoliation in New England are currently unknown. Using dendroecological techniques, this study related annual radial growth of individual host (Quercus spp. and Acer spp.) trees to detailed defoliat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 47 publications
0
15
0
3
Order By: Relevance
“…The significant radial growth divergence between Quercus and P. strobus RWI from 2005-2010 suggests the presence of a stressor that is specific to Quercus. Radial growth analyses of individual trees throughout this region (including at some of the study sites of the present study) found that winter moth defoliation was a strong predictor of radial growth of Quercus trees defoliated by winter moth, when tested concurrently with site and year as random covariates [21]; however, other factors (e.g., other defoliators, pathogens, physical stressors) were not tested. According to Massachusetts aerial detection survey (ADS) data, winter moth defoliation occurred throughout much of eastern Massachusetts from 2004-2011 [11].…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…The significant radial growth divergence between Quercus and P. strobus RWI from 2005-2010 suggests the presence of a stressor that is specific to Quercus. Radial growth analyses of individual trees throughout this region (including at some of the study sites of the present study) found that winter moth defoliation was a strong predictor of radial growth of Quercus trees defoliated by winter moth, when tested concurrently with site and year as random covariates [21]; however, other factors (e.g., other defoliators, pathogens, physical stressors) were not tested. According to Massachusetts aerial detection survey (ADS) data, winter moth defoliation occurred throughout much of eastern Massachusetts from 2004-2011 [11].…”
Section: Discussionmentioning
confidence: 57%
“…While site index and winter moth defoliation only explained 20% and 13%, respectively, of the mortality across our sites, the lack of relationship between stand relative density and % Quercus in dead stems suggests that some density-independent factor may have contributed to some of the mortality noted in our stands. Although we cannot be certain that Quercus mortality was attributable to winter moth and not some other defoliator, pathogen, or physical disturbance, the abundance of winter moth in eastern Massachusetts over the last decade, the known relationship between percent winter moth defoliation and radial growth [21], and the dominance of dead Quercus trees in snag classes 1-3 (and thus the assumption of tree mortality occurring within the 1995-2010 period) collectively implicate winter moth as an important contributor to Quercus mortality in these forests.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The typical damage results in partially defoliated leaves, but can cause lasting damage to the tree. Simmons et al (2014) showed that defoliation by winter moth caused significant decline in tree growth in red oak (Quercus rubra L.) in Massachusetts, as measured by growth rings in increment cores of tree stems. Embree (1967) reported that repeated defoliation by winter moth resulted in as much as 40% tree mortality in red oak stands in Nova Scotia.…”
Section: Figurementioning
confidence: 99%